(11-3m)=10

Simple and best practice solution for (11-3m)=10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (11-3m)=10 equation:


Simplifying
(11 + -3m) = 10

Remove parenthesis around (11 + -3m)
11 + -3m = 10

Solving
11 + -3m = 10

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -11 + -3m = 10 + -11

Combine like terms: 11 + -11 = 0
0 + -3m = 10 + -11
-3m = 10 + -11

Combine like terms: 10 + -11 = -1
-3m = -1

Divide each side by '-3'.
m = 0.3333333333

Simplifying
m = 0.3333333333

See similar equations:

| 13m+-7m-7m=-8 | | X(2x+5)(x-4)=0 | | 5w+3=9 | | 20-3w=11 | | 3x-28-3x-30=33 | | 19=7+3m | | -7-7p=13-4p | | 5m-m+5=17 | | -3=3+2k+4k | | 115b=115 | | -u^2-8u+4=0 | | 8-6x=26 | | 5y-40=-25-5y | | 50+1x=3.50x | | -3(5-3x)+7(-5x-8)=33 | | 20q-17q-3=9 | | 3(5)+2y=1 | | -7x-18-2x=6x+6 | | 3y-2=2(x-6) | | -0.1k=3.1 | | 6-0.75a=0.5a+1 | | -13-22x=31 | | 5-8-2r-5=-15 | | 6+3(5x-6)=8-4(2x+1) | | (x+5)(x-7)=y | | -20+2x=-4x-6+2 | | 5j+6=86 | | X+6+X-2+3x=64 | | 18x^2-2=2 | | 15=4r-1 | | .15x-4=.4x-2 | | 2j+6=16 |

Equations solver categories